2011
DOI: 10.1176/appi.ps.62.10.1225
|View full text |Cite
|
Sign up to set email alerts
|

Underutilization of Mental Health Services Among Bereaved Caregivers With Prolonged Grief Disorder

Abstract: Objective This study examined grief and mental health service use among 86 bereaved caregivers of advanced cancer patients. Methods Caregivers were assessed before (median=3.1 months) and after (median=6.6 months) patients’ deaths for prolonged grief disorder, axis I psychiatric disorders, mental health service use, suicidality, and health-related quality of life. Results Sixteen percent of the bereaved sample met criteria for prolonged grief disorder, which was significantly associated with suicidality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 14 publications
2
38
0
3
Order By: Relevance
“…The focus on grief as a psychiatric disorder is infrequent in the cancer literature, whereas very wide-spread in the more general grief literature [94,95]. This focus corresponds to 25 out of the 76 studies surveyed (33%) [43,[50][51][52][96][97][98][99][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119]. An important body of literature underlines an increased mortality risk for bereaved spouses, particularly through heart disease, cancer, accidents [100], and autoimmune disorders [30,101,102].…”
Section: Grief As a Psychiatric Disorder In The Cancer Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus on grief as a psychiatric disorder is infrequent in the cancer literature, whereas very wide-spread in the more general grief literature [94,95]. This focus corresponds to 25 out of the 76 studies surveyed (33%) [43,[50][51][52][96][97][98][99][103][104][105][106][107][108][109][110][111][112][113][114][115][116][117][118][119]. An important body of literature underlines an increased mortality risk for bereaved spouses, particularly through heart disease, cancer, accidents [100], and autoimmune disorders [30,101,102].…”
Section: Grief As a Psychiatric Disorder In The Cancer Contextmentioning
confidence: 99%
“…Using an epidemiological approach, certain studies focused on identifying predictors of pathological grief reactions. Some studies focused on gender [112], cognitive processes such as negative meaning of the loss [115], alexithymia [116], attachment styles [51,52], and others on the characteristics of caregiving [52,108,109], or place of death (hospital versus hospice) [110]. According to Chiu et al [112], female gender is associated with severe anxiety; however, it is not associated with prolonged grief.…”
Section: Grief As a Psychiatric Disorder In The Cancer Contextmentioning
confidence: 99%
“…Thus, although bereavement can be a highly stressful and significant life experience, most individuals have sufficient internal resources and external support to adequately cope with their grief and slowly readjust to a life without the deceased (Prigerson et al, 2009;Zisook & Shear, 2009). However, research has also shown that for a significant minority of bereaved individuals the grieving process is particularly complicated (e.g., Lichtenthal et al, 2011;Prigerson et al, 2009;Simon et al, 2007). Instead of a decreasing intensity of grief-related distress, these individuals experience severe grief reactions that become abnormally persistent and increasingly debilitating across time (Jordan and Litz, 2014;Maercker et al, 2013;Prigerson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ICs report many barriers to psychosocial service use, including limited time to travel to and from treatment centers, financial constraints, and guilt. As such, in-person supportive services are generally underutilized by ICs, 14 and telehealth is increasingly relied upon for the delivery of support. 15,16 We adapted MCP-C for delivery over the Internet to attend to the documented barriers to engaging ICs in in-person support.…”
mentioning
confidence: 99%